2006
DOI: 10.1096/fj.05-4682rev
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans and their proteoglycans: host‐associated molecular patterns for initiation and modulation of inflammation

Abstract: Glycosaminoglycans, linear carbohydrates such as heparan sulfate and hyaluronan, participate in a variety of biological processes including cell-matrix interactions and activation of chemokines, enzymes and growth factors. This review will discuss progress in immunology and the science of wound repair that has revealed the importance of glycosaminoglycans, and their proteoglycans, in the inflammatory process. Heparan sulfate enables growth factor function and modifies enzyme/inhibitor functions, such as antith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
470
0
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 560 publications
(492 citation statements)
references
References 132 publications
(226 reference statements)
5
470
0
17
Order By: Relevance
“…Kawashima et al reported that oversulfated chondroitin/dermatan sulfate chains are important in selectin-and/or chemokine-mediated cellular responses [7]. In addition, hyaluronan alternatively participates in leukocyte recruitment via interaction with CD44, while activating various inflammatory cells, such as macrophages, through CD44-dependent signaling [8]. Therefore, the field of polysaccharide biology provides new clues and explanations of the process of inflammation and suggests new therapeutic approaches to human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Kawashima et al reported that oversulfated chondroitin/dermatan sulfate chains are important in selectin-and/or chemokine-mediated cellular responses [7]. In addition, hyaluronan alternatively participates in leukocyte recruitment via interaction with CD44, while activating various inflammatory cells, such as macrophages, through CD44-dependent signaling [8]. Therefore, the field of polysaccharide biology provides new clues and explanations of the process of inflammation and suggests new therapeutic approaches to human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Chondroitin sulfate proteoglycans (CSPGs) are a family of extracellular matrix (ECM) molecules with diverse functions in development (Bandtlow and Zimmermann, 2000;Schwartz and Domowicz, 2004), infection (Uyama et al, 2006), inflammation (Taylor and Gallo, 2006), and tissue morphogenesis and cell division (Mizuguchi et al, 2003). Of these, the role of CSPGs in mammalian CNS injury and plasticity has been the subject of intense investigation (Carulli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…HS is a highly sulfated polysaccharide consisting of the repeating disaccharide unit of 1→4-linked glucosamine and glucuronic/iduronic acid that may contain sulfo groups. A large body of evidence has demonstrated that this highly sulfated polysaccharide plays roles in regulating embryonic development, inflammatory responses, assisting viral and bacterial infections as well as blood coagulation (1)(2)(3)(4)(5). Under physiological pH, the sulfo groups exhibit considerable negative charges that influence binding properties to more than one hundred proteins.…”
Section: Introductionmentioning
confidence: 99%